(NpOSELENIQ \POHI NEOLITA I RANNEGO METALLA W PRIUSTXE REKI |MAJYGI (B((N|STONSKOJ ssr(B) /s - (NqNITS(B, (Nl(B.(N`(B.s; (NiNSTITUT ISTORII an |ssrs ((NtALLIN (B:s (Nb(B. (NI(B.,s, 1959)
(NrEZ@ME NA NEM(B. (NQZ(B.s
(NbIBLIOGR(B.: (NS(B. 372-379s
Keywords: (NnEOLIT s -- (N|STONIQs; (NaRHEOLOGI^ESKIE PAMQTNIKI s -- (N|STONIQs